A prospective cohort study of infertility and cancer incidence - Wang, Siwen; Gaskins, Audrey J; Farland, Leslie V; Zhang, Dan; Birmann, Brenda M; Rich-Edwards, Janet W; Wang, Yi-Xin; Tamimi, Rulla M; Missmer, Stacey A; Chavarro, Jorge E (Fertility and sterility, 2023)
To investigate the association between infertility and the incidence of invasive cancer. Prospective cohort study (1989-2015). Not applicable. A total of 103,080 women aged 25-42 years in the Nurses' Health Study II who were cancer-free at baseline (1989). The infertility status (failure to conceive after 1 year of regular, unprotected sex) and causes of infertility were self-reported at baseline and biennial follow-up questionnaires. Cancer diagnosis was confirmed through medical record review and classified as obesity-related (colorectal, gallbladder, kidney, multiple myeloma, thyroid, pancreatic, esophageal, gastric, liver, endometrial, ovarian, and postmenopausal breast) or non-obesity-related (all other cancers). We fit the Cox proportional-hazards models to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) of the association between infertility and cancer incidence. During 2,149,385 person-years of follow-up, 26,208 women reported a history of infertility, and we documented 6,925 incident invasive cancer cases. After adjusting for body mass index and other risk factors, women who reported infertility had a higher risk of developing cancer than gravid women without a history of infertility (HR, 1.07; 95% CI, 1.02-1.13). This association was stronger among obesity-related cancers (HR, 1.13; 95% CI, 1.05-1.22; vs. non-obesity-related cancers, HR, 0.98; 95% CI, 0.91-1.06) and, in particular, obesity-related reproductive cancers (postmenopausal breast, endometrial, and ovarian cancers; HR, 1.17; 95% CI, 1.06-1.29) and was stronger among women who first reported infertility earlier in life (≤25 years, HR, 1.19; 95% CI, 1.07-1.33; 26-30 years, HR, 1.11; 95% CI, 0.99-1.25; >30 years, HR, 1.07; 95% CI, 0.94-1.22; P trend < .001). A history of infertility may be associated with the risk of developing obesity-related reproductive cancers; further study is needed to elucidate the underlying mechanisms.